Association study of variants in genes FTO, SLC6A4, DRD2, BDNF and GHRL with binge eating disorder (BED) in Portuguese women. (March 2019) - Palmeira, Lara; Cunha, Marina; Padez, Cristina; Alvarez, Manuela; Pinto-Gouveia, José; Manco, Licínio
Highlights: No significant associations with BED were found for FTO, SLC6A4, DRD2, BDNF and GHRL . DRD2 rs1800497 could be a potential marker of obesity. The FTO rs9939609 obesity risk A-allele has no potential role in BED. Abstract: A population based case-control study was conducted in Portuguese women with overweight/obesity to investigate the possible association of variants in genes FTO, SLC6A4, DRD2, BDNF and GHRL with binge eating disorder (BED). The distribution of seven polymorphisms was evaluated in 31 BED patients and 62 controls. No significant associations were found between polymorphisms and BED. Of interest, a markedly lower frequency of the FTO rs9939609 obesity risk A-allele was found in BED patients (0.290) in relation to the control group (0.402). Contrasting with anorexia nervosa and bulimia nervosa, our data suggest that rs9939609 A-allele has no potential role in BED.